Effects of Ph on Calcium Carbonate Precipitation Under Magnetic Field - Saksono, Nelson; Yuliusman, Yuliusman; Bismo, Setijo; Soemantojo, Roekmijati W.; Manaf, Azwar (Makara Journal of Technology, 2009)
Magnetic field effect on CaCO3 precipitation is the key parameter in evaluating the effectiveness of Anti-scale Magnetic Treatment (AMT). The purpose of this study was to investigate magnetic fields influence on CaCO3 precipitation in high and low super-saturated CaCO3 solution by varied pH CaCO3 solution using circulation flow fluid system. The observation results in the high super saturated solution (pH 8.5) showed the increase of precipited CaCO3 in magnetized solutions compared to those in non-magnetic solution during circulation process. In the low super-saturated CaCO3 solution (pH 6.4) it was found that magnetic treatment increased CaCO3 precipitation after circulation process. In high super-saturated solution, magnetic field strengthens ion interactions, which reduce precipitation during circulation process. However, in low super-saturated CaCO3 solution, magnetic field weakens hydrate ion interaction which indicated by decreasing of the conductivity of solution. It increases the precipitation of CaCO3 after the circulation of magnetization process has completed.